Integration of Hepadnavirus DNA in Infected Liver: Evidence for a Linear Precursor - Yang, Wengang (American Society for Microbiology, 1999)
DNA of the avian hepadnavirus, duck hepatitis B virus, was found to be integrated at low abundance into the cellular DNA extracted from the livers of infected ducklings. The frequency of integration was estimated to be at least one viral genome per 10(3) to 10(4) cells by 6 days postinfection. The structures of virus-cell junctions determined by sequencing were compared with those of virus-virus junctions formed by nonhomologous recombination between the ends of linear viral DNA forms. This comparison allowed us to conclude that linear viral DNA was the preferential form used as an integration substrate. Potential factors promoting viral DNA integration during chronic infection are discussed.